THE USE OF THE ROLE PLAYING METHOD IN INDONESIAN THEMATIC SUBJECTS TO IMPROVE THE SPEAKING ABILITY OF CLASS 3 STUDENTS AT SDN 1 AMBARAWA - Iwan Agesta; Eri Purwanti; Tuti Puspitasari (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Abstract This study aims to improve the speaking skills of grade 3 students through the role playing method at SDN 1 Ambarawa. This research uses Classroom Action Research (CAR) which uses a quantitative descriptive method using the Kemmis and Mc research model. Taggart, which consists of 2 cycles and each cycle has four stages, namely: planning, implementing, observing, and reflecting. For data checking, obtained from the results of observations that have been made by researchers from each course of learning speaking skills and when using the role playing method. The subjects in this study were class III students at SDN 1 Ambarawa with a total of 25 students consisting of 10 male students and 15 female students. The percentage of classical achievement increased drastically from 28% in pre-cycle to 76% in cycle I, and then increased again to 92% in cycle II. There was an increase in the comparison of class average scores from each cycle. In the pre-cycle, the average student score was 63.36, while in the first cycle there was a significant increase in the class average score to 77.08. Furthermore, in cycle II, there was a greater increase in the class average score for speaking skills, reaching 83.24. These results prove that the role playing method is very effective in improving students' speaking skills. Keywords: Speaking Ability, Role Playing Method